Infrared optical properties of nanoantenna dimers with photochemically narrowed gaps in the 5 nm regime - Neubrech, Frank; Weber, Daniel; Huck, Christian; Pucci, Annemarie (ACS nano, 2012)
In this paper, we report on the manipulation of the near-field coupling in individual gold nanoantenna dimers resonant in the infrared (IR) spectral range. Photochemical metal deposition onto lithographically fabricated nanoantennas is used to decrease the gap between the antenna arms down to below 4 nm, as confirmed by finite-difference time-domain simulations. The increased plasmonic coupling in the gap region leads to a shift of the surface plasmon resonances to lower energies as well as to the appearance of hybridized plasmonic modes. All of the occurring electron oscillation modes can be explained by the plasmon hybridization model. Besides the bonding combination of the fundamental resonances of individual antennas, also the antibonding combination is observed in the IR transmittance at normal incidence. Its appearance is due to both structural defects and the small gaps between the antennas. The detailed analysis of individual IR antennas presented here allows a profound understanding of the spectral features occurring during the photochemical manipulation process and therefore paves the way to a full optical process monitoring of sub-nanometer scale gaps, which may serve as model systems for experimental studies of quantum mechanical effects in plasmonics.
Gesehen am 10.04.2018